Conversor ca-cc multinível de estágio integrado para aplicação em transformadores de estado sólido - Araújo, José Willamy Medeiros de (2022)
This work proposes the study and development of an integrated stage multi-level AC-DC converter for application in solid-state transformers. The converter has bidirectional capability and can be modularized for medium voltage application with three modules per phase, each cell being composed of a converter containing a dual active bridge (DAB) and an interleaving structure. A qualitative analysis is performed showing the modulation technique as well as the control strategy needed for the converter. A new multivariable magnetization control is proposed for the correct operation of the converter. A quantitative analysis is performed determining the AC current ripple, capacitor voltage ripple and the semiconductors efforts as well as the losses analysis. The necessary design procedures for the construction of the prototype are discussed, highlighting the fiber optic insulation, calculation time and modulator. Finally, the validation of the study is carried out through simulation and experimental results. A great similarity is obtained between the developed modeling and simulation. The bidirectionality of the structure and the control loops dynamics are validated through power flow inversion tests with an accommodation time of less than 500 ms. Experimental results with one module, three modules in a single phase and one module per phase in a three-phase system are presented with great similarity with the simulation, validating the necessary characteristics for the solid state transformer application. The topology is capable of operating with unity power factor and THD of 2.84% for one module and 4.62% for the three-phase structure. The efficiency curve of the converter is shown, reaching a maximum efficiency of 97% and 95.2% in rated condition. A correct balance of the modules is obtained, as well as a balance of the currents synthesized in the three-phase system. The developed magnetization control loop is of great importance considering that the converter was not able to reach the rated regime without it. Comparisons with other structures are performed demonstrating the advantages and disadvantages of the converter